Penafsiran Al-Qur’an: Mencari Keseimbangan Antara Teks dan Konteks dalam Menafsirkan Al-Qur’an - Agung Nugroho Reformis Santono; Anshori Anshori; Nginayaturrohmah Nginayaturrohmah (Asosiasi Ilmu Alquran dan Tafsir se-Indonesia, 2024)
Controversies surrounding the interpretation of Qur’anic verses through textual and contextual approaches have intensified, sparking intense debate among scholars, practitioners, and having widespread social implications. Interpretations that focus solely on the textual dimension, without considering the historical and sociocultural contexts, frequently lead to misunderstandings and may even be exploited by certain groups to justify extremist acts. Conversely, the contextual approach provides a more inclusive alternative by emphasizing the relevance of Qur’anic values to contemporary challenges, though it often faces criticism for allegedly compromising textual authenticity. This study aims to propose a synthesis of both approaches in order to achieve a more comprehensive and responsive understanding. Employing a library-based research method and critical analysis of pertinent literature on these two interpretive typologies, the findings indicate that integrating textual and contextual perspectives can prevent distorted interpretations, preserve textual authenticity, and simultaneously address social dynamics. As a result, the understanding of the Qur’an is no longer trapped in a rigid textual-contextual dichotomy but rather moves toward a more balanced and adaptive interpretation